2011
DOI: 10.3109/09637486.2010.534078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of operating conditions in freeze-drying on the nutritional properties of blueberries

Abstract: The effect of particle size, use of infrared radiation, and type of freeze-drying (vacuum or atmospheric) on some nutritional properties of blueberries was investigated. Ascorbic acid was decreased in freeze-dried blueberries compared with fresh fruit, while polyphenols were decreased in atmospheric freeze-drying-unlike in vacuum freeze-drying, where this nutritional property was increased. Antioxidant activity of freeze-dried blueberries did not differ significantly from that found in fresh fruits. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…Reyes et al (2009) also reported an increase in DPPH antioxidant activity (EC 50 ) and a decrease in polyphenols when murtilla fruits from ecotype 14-4 INIA from the Carillanca Genetic Bank were evaluated by vacuum and atmospheric freeze drying. Additionally, the antioxidant efficiency (1/EC 50 ) was not significantly affected in dried blueberry fruits prepared by vacuum or atmospheric freeze drying (Reyes et al, 2011).…”
Section: Antioxidant Activity In Fresh and Dried Murtilla Fruit By Dpmentioning
confidence: 88%
“…Reyes et al (2009) also reported an increase in DPPH antioxidant activity (EC 50 ) and a decrease in polyphenols when murtilla fruits from ecotype 14-4 INIA from the Carillanca Genetic Bank were evaluated by vacuum and atmospheric freeze drying. Additionally, the antioxidant efficiency (1/EC 50 ) was not significantly affected in dried blueberry fruits prepared by vacuum or atmospheric freeze drying (Reyes et al, 2011).…”
Section: Antioxidant Activity In Fresh and Dried Murtilla Fruit By Dpmentioning
confidence: 88%
“…This is in accordance with Reyes et al . (), who showed that ascorbic acid content was decreased in freeze‐dried blueberries compared with fresh fruit, while polyphenols were decreased in atmospheric freeze‐drying unlike in vacuum freeze‐drying, where this nutritional property was increased. The results show promising perspectives for the exploitation of berry species with considerable levels of nutrients and antioxidant capacity in foods.…”
Section: Discussionmentioning
confidence: 99%
“…Cranberry was investigated as a chemotherapeutic agent (Elberry et al, 2010). The effect of particle size, use of infrared radiation and type of freeze-drying (vacuum or atmospheric) on some nutritional properties of blueberries was investigated (Reyes et al, 2011). The purpose of some studies was to investigate and compare the composition, stability and antioxidant properties of berry extracts from selected cultivars using some extraction methods (Chanda & Kaneria, 2012;Khoo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…fao.org). Whereas modern processing techniques such as freezedrying or microwave-vacuum drying are promising to increase the stability of nutritionally relevant compounds in raw materials (Böhm, Kühnert, Rohm, & Scholze, 2006;Reyes et al, 2011), it is formulation which needs to be modified to obtain energy-reduced, fibre-enriched products. Lifestyle intervention, including dietary modification (increased whole grains, fibre, vegetables, and fruit; reduced total and saturated fat, sugar, and refined grains) and physical activity, shows a significant potential for preventing type 2 diabetes (Tuomilehto, Schwarz, & Lindström, 2011), and weight reduction among overweights was also reported as predictor of decreased diabetes risk (Hamman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%